Skin microbiome differences relate to the grade of acne vulgaris. Issue 9 (10th July 2019) - Li, Chun‐xi; You, Zhi‐xuan; Lin, Yan‐xia; Liu, Hai‐yue; Su, Jin
Abstract: The skin microbiome plays important roles in the pathogenesis and development of acne. We aimed to investigate the facial skin microbiome of acne and microbiome differences related to different grades of acne. Skin swabs from nine healthy controls and 67 acne patients were collected, and the skin microbiomes were analyzed using 16S rRNA gene sequencing. Compared with healthy controls, acne patients harbored significantly altered skin microbiomes. The skin microbiomes of patients with grade 1–3 acne were similar, but patients with grade 4 acne showed a significantly different skin microbiome compared with grade 1–3 acne, including increased alpha diversity and increased proportions of four Gram‐negative bacteria ( Faecalibacterium, Klebsiella, Odoribacter and Bacteroides ). In conclusion, acne patients harbored an altered skin microbiome, and more significant dysbiosis was found in patients with grade 4 acne (severe acne). Our findings may provide evidence for the pathogenic mechanisms of acne and microbial‐based strategies to avoid and treat acne, especially grade 4 acne.